Visual Essay: The City Hides the Process. Popular Protest in ‘Vila Autodromo’, Rio de Janeiro - Claudia Villegas; Khalil Esteban; Beatriz Nussbaumer (Íconos)
Visual Essay "The City Hides the Process. Popular Protest in ‘Vila Autodromo’, Rio de Janeiro."